Pre-Pilot and Pilot Studies with Malaysian Nurses on Transnational Nurse Education - Arunasalam, Nirmala Devi (Border Crossing, 2017)
This article reports on research undertaken to identify Malaysian nurses’ experiences of the part-time Transnational Higher Education post-registration top-up degree programmes delivered by one Australian and two UK universities. An interpretive paradigm and hermeneutic phenomenology and ethnographic principle of cultural interpretation research designs were used. A mixed methods approach was chosen, using both quantitative and qualitative methods. The Bristol Online Survey Questionnaire (BOS) and semi-structured interviews were initially selected to collect data. Pre-pilot testing refined the quantitative and qualitative data collection tools. However, the pilot study for BOS failed to elicit useful responses. This led to only the qualitative methodology being used to elicit participants’ views in a culturally sensitive way. The interview guide allowed nurses’ views of their experiences in relation to the research question to be obtained. This study adds to the knowledge and insight on pre-pilot and pilot studies in international multicultural studies in Asia.